2021
DOI: 10.6061/clinics/2021/e3022
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of pre-thyroidectomy neutrophil–lymphocyte, platelet–lymphocyte, and monocyte–lymphocyte ratios for discriminating lymph node and distant metastases in differentiated thyroid cancer

Abstract: This study aimed to analyze the relationship of neutrophil-lymphocyte ratio (NLR), plateletlymphocyte ratio (PLR), and monocyte-lymphocyte ratio (MLR) with clinicopathological characteristics of patients with differentiated thyroid cancer (DTC). METHODS: This retrospective study included 390 patients with DTC who had complete blood cell counts available at the time of surgery. NLR, PLR, and MLR were calculated, and the risk of cancer-related death, structural recurrence, and response to therapy were assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…A higher relative ratio of monocytes in THCA patients tends to be associated with a higher risk of postoperative recurrence, [ 45 ] and the relative ratio is also higher in THCA patients with lymph node and distant metastases. [ 46 ] Gogali F et al [ 47 ] found higher NK cell infiltration levels in papillary thyroid carcinoma (PTC) tissues, and NK cell infiltration levels were positively correlated with PTC clinical stage. In addition, vascular endothelial growth factor (VEGF) produced by tumor cells can effectively stimulate endothelial cell proliferation and angiogenesis, and plays a key role in the pathophysiology of THCA.…”
Section: Discussionmentioning
confidence: 99%
“…A higher relative ratio of monocytes in THCA patients tends to be associated with a higher risk of postoperative recurrence, [ 45 ] and the relative ratio is also higher in THCA patients with lymph node and distant metastases. [ 46 ] Gogali F et al [ 47 ] found higher NK cell infiltration levels in papillary thyroid carcinoma (PTC) tissues, and NK cell infiltration levels were positively correlated with PTC clinical stage. In addition, vascular endothelial growth factor (VEGF) produced by tumor cells can effectively stimulate endothelial cell proliferation and angiogenesis, and plays a key role in the pathophysiology of THCA.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the highest Post-PLR (Post-PLR-H) was the significant parameter associated with DM and an independent prognostic factor of DC rates. The association between a high PLR and poor prognosis has been demonstrated in several types of solid tumors [ 20 , 22 , 25 , 29 , 30 , 31 , 32 , 33 , 35 , 36 , 54 ]. However, treatment types, including immunotherapy, chemotherapy, RT, or surgery, varied among studies, and the majority of the studies focused on the pretreatment value of PLR.…”
Section: Discussionmentioning
confidence: 99%
“…However, treatment types, including immunotherapy, chemotherapy, RT, or surgery, varied among studies, and the majority of the studies focused on the pretreatment value of PLR. Very recently, a relationship between high PLR and distant organ metastasis in various types of cancers including breast, esophageal, hepatocellular, prostate, and thyroid cancer has been reported [ 32 , 33 , 34 , 35 , 55 ]. Our study results also support this theory of a robust role of PLR in the development of DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The histological subtype, tumour differentiation of the tumour, immunohistochemistry, genomics, epigenomics, metabolomics and the changes in the micro-environment of the tumour also have an influence on the prognosis of WDTC and therefore guide of appropriate treatment [ 26 , 27 , 28 , 41 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Additional markers that have been found to be useful in the risk stratification of patients with TC include serum Vitamin D and the neutrophil-to-lymphocyte ratio (NLR) [ 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%